Nowe media a nowe gatunki – wstępna charakterystyka genologiczna internetowego forum dyskusyjnego - Naruszewicz-Duchlińska, Alina (Postscriptum Polonistyczne, 2020)
The article presents the main elements from a discussion forum that examined the Internet as a genre from the perspective of linguistic genology. This genre is presented as a codified one, which meets technological requirements, accepted textual standards and norms of communication (netiquette, regulations). It is an asynchronous form, which operates in hypertextual mode, though oral elements can also be distinguished. The following elements are characteristic of Internet discussion forums: dialogic aspect, petrification of textual frame, thematic arrangements, colloquial character and a tendency to condense both form and content. The main purpose of Internet discussion forums is to present and share information and opinions.